Assessment of a Potential Role of Dickeya dadantii DSM 18020 as a Pectinase Producer for Utilization in Poultry Diets Based on in silico Analyses - Dittoe, Dana K.; Barabote, Ravi D.; Rothrock, Michael J.; Ricke, Steven C. (Frontiers in Microbiology, 2020)
Currently, the poultry industry has been faced with consumer pressure to utilize only vegetable feedstuffs in poultry diets, eliminate antibiotics from poultry production, and rear poultry in free range systems. To maintain current production standards, the industry must determine ways to enhance nutrient uptake and utilization further. One possible solution is the supplementation of pectinase, an enzyme that degrades pectin within the cell walls of plants, in poultry diets. Therefore, the objective of the current study was to determine the potential role of a pectinase producer, Dickeya dadantii DSM 18020, as a commercially utilized pectinase producer in poultry diets against other known pectinase producers, in silico. In the current study, whole genomes of Dickeya dadantii DSM 18020 (Dd18020), D. dadantii 3937 (Dd3937), D. solani IPO 2222 (Ds2222), Bacillus halodurans C-125 (BhC125), and B. subtilis subsp. subtilis str. 168 (Bs168) were compared using bioinformatic approaches to compare the chromosomal genome size, GC content, protein coding genes (CDS), total genes, average protein length (a.a.) and determine the predicted metabolic pathways, predicted pectin degrading enzymes, and pectin-degradation pathways across pectinase producers. Due to insufficient information surrounding the genome of Dd18020 (lack of annotation), the genome of Dd3937, a 99% identical genome to Dd18020, was utilized to compare pectinase-associated enzymes and pathways. The results from the current study demonstrated that Dd3937 possessed the most significant proportion of pathways presented and the highest number of pathways related to degradation, assimilation, and utilization of pectin. Also, Dd18020 exhibited a high number of pectinase-related enzymes. Both Dd3937 and Dd2222 shared the pectin degradation I pathway via the EC 3.1.1.11, EC 3.2.1.82, and EC 4.2.2.- enzymes, but did not share this pathway with either Bacillus species. In conclusion, Dd18020 demonstrated the genetic potential to produce multiple pectinase enzymes that could be beneficial to the degradation of pectin in poultry diets. However, for Dd18020 to become a commercially viable enzyme producer for the poultry industry, further research quantifying the pectinase production in vitro and determining the stability of the produced pectinases during feed manufacturing are necessary.